2018
DOI: 10.24252/eternal.v42.2018.a10
|View full text |Cite
|
Sign up to set email alerts
|

Describing and Drawing Picture Technique in Teaching Transactional Speaking

Abstract: The research aimed to find out the effectiveness of describing and drawing picture technique in teaching transactional speaking at the second semester students of English Education Department at State Islamic University of Alauddin Makassar. This research employed quasi-experimental with non-equivalent control group design with pre-test and post-test. The population of this research was the second semester students of English education department at State Islamic University of Alauddin Makassar. The population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Using drawing picture as a media showed that students have gained a deeper comprehension of their own concepts and made an effort to express their views clearly. By using drawing picture all students have chance to practice their speaking ability in the class and encourage students to communicate smoothly (Nur, 2018).…”
Section: Table 2 the Results Of Students' Perception Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Using drawing picture as a media showed that students have gained a deeper comprehension of their own concepts and made an effort to express their views clearly. By using drawing picture all students have chance to practice their speaking ability in the class and encourage students to communicate smoothly (Nur, 2018).…”
Section: Table 2 the Results Of Students' Perception Analysismentioning
confidence: 99%
“…The media used makes it easier for students to learn and master English vocabulary because of the concrete examples (Ristyani & Nurhayati, 2020). Drawing Picture Media effectively stimulates students' brain performance in understanding based on visualizing (Nur, 2018). In addition, students feel motivated to pay attention and participate in the learning process to make the class more active (Mumtahabah, 2014).…”
Section: | English Educationmentioning
confidence: 99%
See 1 more Smart Citation